2001
DOI: 10.1021/ma0106651
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Bipyridyl-Containing Conjugated Polymers:  Effects of Polymer Rigidity on Metal Ion Sensing

Abstract: Three conjugated polymers comprised of 9,9-dioctylfluorene and 2,2‘-bipyridine, which are alternatively linked by the C−C single bond (P1), vinylene bond (P2), or ethynylene bond (P3), have been synthesized via the Suzuki reaction, the Wittig−Horner reaction, and the Heck reaction, respectively. The optical, electrochemical, and other physical properties of the polymers are dependent on the linkers. The polymer linked by the C−C single bond exhibits a much larger Stokes shift compared with the other two polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
136
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(142 citation statements)
references
References 32 publications
5
136
0
1
Order By: Relevance
“…[12][13][14] Among them, conjugated pyridine-incorporated polymers have attracted much attention owing to the possibility of finetuning the optical properties by means of 1) the electron-accepting ability, 2) N-protonation, 3) N-oxidation, 4) N-alkylation, and 5) metal complexation. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] p-Conjugated polymers that incorporate aryl heterocyclic units, such as pyridine, pyrrole, and thiophene rings, have been synthesized and employed in industrial applications. [30][31][32][33][34] The laddertype polymers incorporated with pyrazines, [35] benzothiadazoles, [36] pyrroloimides, [37] pyridobisimidazoles, [38] and benzothiazole [39] that contain intramolecular hydrogen bonds along the polymer backbone are also known in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] Among them, conjugated pyridine-incorporated polymers have attracted much attention owing to the possibility of finetuning the optical properties by means of 1) the electron-accepting ability, 2) N-protonation, 3) N-oxidation, 4) N-alkylation, and 5) metal complexation. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] p-Conjugated polymers that incorporate aryl heterocyclic units, such as pyridine, pyrrole, and thiophene rings, have been synthesized and employed in industrial applications. [30][31][32][33][34] The laddertype polymers incorporated with pyrazines, [35] benzothiadazoles, [36] pyrroloimides, [37] pyridobisimidazoles, [38] and benzothiazole [39] that contain intramolecular hydrogen bonds along the polymer backbone are also known in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…[8] The synthesis of conjugated polymers with bipyridine/phenanthroline moieties or crown ethers or a combination of both groups have already been reported in the literature. [8,15,46] Our research efAbstract: We report on the synthesis and characterization of a series of asymmetrically functionalized amphiphilic polymers with alternating pdonor units (e.g., substituted benzene) and p-acceptor units (e.g., pyridine) along the polymer backbone. The purpose of our present work involves incorporation of functional groups along the main chain to form intrachain hydrogen bonds, which promote planarization of the polymer backbone, and to fine-tune the optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al reported three bipyridyl-based polymers, in which the bipyridyl and fluorene units were directly bonded with vinylene and ethynylene bond spacers, respectively (see Figure 6). 17 The effect of the different spacers on the spectral response to metal ions was studied by using the bipyridyl unit as the complexation site. It was found that the polymer P6 without any spacers provided the weakest resistance to the coplanarity of the two pyridine rings unit during the complexation with metal ions, and thus gave the highest response and sensitivity to the metal ions.…”
Section: Chemosensors Based On Conjugated Polymersmentioning
confidence: 99%
“…The relatively small Stokes shifts (34 nm for P1, 35 nm for P2 and 26 nm for P3 nm) between the absorption and emission maximum wavelengths of the polymers, P1, P2, and P3 indicate the rigidity of the conjugated polymer backbone which hinders deformation in going from the ground to the excited state. 26 Thermal Properties Thermal stability of the polymers P1, P2, and P3 were evaluated by TGA under nitrogen gas flow and their TGA curves are illustrated in Figure 3. Polymer P1 displays a main decomposition at 455 C due to the scission of alkly side chains from the polymer backbone [ Fig.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…These features make them suitable in sensing biologically and environmentally important metal ions selectively and at low detection limits. [26][27][28][29][30][31][32] For instance, C-9 position of fluorene was functionalized with various groups such as phosphonates, sulfonates, and dendronized amino acids and subsequently these monomers were polymerized using Suzuki Coupling reactions to obtain water soluble blue emitting polymers which can be utilized as chemosensors. [29][30][31][32] It was shown that the PF with having phosphonates 30 and sulfonates 31 .…”
mentioning
confidence: 99%